2016
DOI: 10.1038/srep32982
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for a precise analysis of subchondral bone alterations

Abstract: Subchondral bone alterations are emerging as considerable clinical problems associated with articular cartilage repair. Their analysis exposes a pattern of variable changes, including intra-lesional osteophytes, residual microfracture holes, peri-hole bone resorption, and subchondral bone cysts. A precise distinction between them is becoming increasingly important. Here, we present a tailored algorithm based on continuous data to analyse subchondral bone changes using micro-CT images, allowing for a clear defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…According to a micro-CT based algorithm for the analysis of subchondral bone changes following microfracture treatment25, no intra-lesional osteophytes and subchondral bone cysts were detected in defects from any treatment group. Residual microfracture holes and peri-hole bone resorption were frequently observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a micro-CT based algorithm for the analysis of subchondral bone changes following microfracture treatment25, no intra-lesional osteophytes and subchondral bone cysts were detected in defects from any treatment group. Residual microfracture holes and peri-hole bone resorption were frequently observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the micro-CT image dataset of each osteochondral specimen, the presence of subchondral bone alterations was described and qualitatively evaluated25. The reported types of subchondral bone changes included intra-lesional osteophytes, residual microfracture holes, peri-hole bone resorption, and subchondral bone cysts.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional posterolateral approach (PLA) is the most widely applied approach with excellent exposure for both primary and revision hip arthroplasty [6, 7]. However, previous studies reported high risks of postoperative dislocations and periprosthetic fractures associated with the posterior approach possibly due to the extensive intraoperative impairment of periarticular soft tissues, particularly the external rotators and joint capsule [811].…”
Section: Introductionmentioning
confidence: 99%
“…In the ovine model, such pathological osteochondral alterations may be examined at very high resolutions with micro-computed tomography (micro-CT), besides macro- and microscopic analyses. Micro-CT is capable of virtually separating the acquired samples into 2-dimensional (2-D) sections and allows for an objective measurement of the 3-dimensional (3-D) microarchitecture on a microscopic scale 9 13 , a possibility not feasible in clinical settings 10 , 11 , 13 17 . Moreover, 3-D image registration is available to aid with the problem of identical sample orientation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%